Pengaruh Media Audiovisual Dalam Meningkatkan Kemampuan Maharah Istima’ Kelas VII MTs Darul Ulum Waru - Hafi, Achmad; Jannah, Ida Miftakhul; Halim, Abdul (WASIS : Jurnal Ilmiah Pendidikan, 2025)
This study aims to investigate the effect of using audiovisual media on improving the maharah istima’ (listening skills) of seventh-grade students at MTs Darul Ulum Waru Sidoarjo. The background of this research highlights the importance of mastering maharah istima’ in Arabic language learning and the need for innovative, engaging, and interactive learning media. The research employed a quantitative method with a pre-experimental one-group pretest-posttest design. The study was conducted at MTs Darul Ulum Waru Sidoarjo involving 30 seventh-grade students as subjects. Data were collected through maharah istima’ ability tests and observation of student learning activities. The instrument used was a validated Arabic listening comprehension test. Data analysis utilized the paired sample t-test with the assistance of SPSS software to determine whether there was a significant difference between pretest and posttest results. The results showed an increase in the students' average scores from 73.23 in the pretest to 86.57 in the posttest. Hypothesis testing with the paired sample t-test revealed a significance value of 0.000 < 0.05, indicating a significant effect of audiovisual media on students’ maharah istima’ abilities. Therefore, audiovisual media proved to have a significant impact as a learning medium that enhances students’ listening skills in Arabic.